Characterization of the recognition site and diagnostic potential of an enterovirus group-reactive monoclonal antibody. - Samuelson, A (1995)
The epitope for a monoclonal antibody reactive against different enteroviruses was characterized. The epitope could be located to residues 40 to 48 of VP1, and the most-essential residues for monoclonal antibody binding coincided with those conserved among the majority of known enteroviruses, indicating a high diagnostic potential.